1993
DOI: 10.1002/1097-0142(19930601)71:11<3570::aid-cncr2820711118>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of steroid hormone receptors for 5-year survival in stage II endometrial cancer

Abstract: Background and Methods. In a prospective study, the 5‐year survival of 57 patients with Stage II endometrial cancer was correlated to the estrogen (ER) and progesterone (PR) receptor concentrations using the dextran‐coated charcoal (DCC) technique. The cutoff level was 3 fmol/mg of protein for ER and 6 fmol/mg of protein for PR. Results. An histopathologic examination of the tumor tissue samples before treatment demonstrated that 16% of the cases (9 patients) were well‐differentiated (Grade 1), 45% (26 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The reported incidence of ER and PR in endometrial carcinomas varies in several series from 35% to 70% [9,13,32,44,46], and our results are at the lower end of this range, sharing, in accordance with other studies [5,9,20], a frequent co-expression of both receptors. In most series, the lack of ER and PR expression by endometrial tumour cells has been a marker of aggressive tumour behaviour and, indeed, many investigators connected the loss of hormone dependence with nonendometrioid-type carcinomas [4,22] or with poorly differentiated endometrial tumours and advanced stage of disease [5,10,12,13,20,25,42]. In this series, the receptor status was unrelated to tumour differentiation or the stage of disease, but it was certainly related to the non-endometrioid carcinomas and deep myometrial invasion, particularly ER loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported incidence of ER and PR in endometrial carcinomas varies in several series from 35% to 70% [9,13,32,44,46], and our results are at the lower end of this range, sharing, in accordance with other studies [5,9,20], a frequent co-expression of both receptors. In most series, the lack of ER and PR expression by endometrial tumour cells has been a marker of aggressive tumour behaviour and, indeed, many investigators connected the loss of hormone dependence with nonendometrioid-type carcinomas [4,22] or with poorly differentiated endometrial tumours and advanced stage of disease [5,10,12,13,20,25,42]. In this series, the receptor status was unrelated to tumour differentiation or the stage of disease, but it was certainly related to the non-endometrioid carcinomas and deep myometrial invasion, particularly ER loss.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Kauppila and colleagues found that the simultaneous presence of ER and PR is associated with a favourable survival for stage-I and -II endometrial tumours [20], and others extended this observation to include recurrent or advanced stage endometrial disease [5,7,9]. Others found that ER [5,13] or PR alone [10] is a better indicator of prognosis, and still others failed to attach any prognostic significance in the receptor status of endometrial malignancies [12,25]. In an earlier study, with a 10-year follow-up, we found a significant relationship between a high PR or ER/PR content and an improved disease-free survival in patients with endometrial carcinoma, but these results were based on the detection of cytoplasmic, rather than nuclear, receptors [41].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested that the progesterone receptor (PR)/ER concentration is significant as a prognostic parameter for endometrial cancer (Friberg and Noren, 1993;Kadar et al, 1993;Morris et al, 1995;Moutsatsou and Sekeris 1997), and that PR status significantly predicts the disease-free survival of patients with endometrial cancer. It has been shown that lymph node metastasis from endometrial cancer is correlated with negative PR protein expression (Iwai et al, 1999).…”
mentioning
confidence: 99%